2019
DOI: 10.5114/kitp.2019.83940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking history on postoperative complications after lung cancer surgery – a study based on 286 cases

Abstract: Aim The aim of the study was to evaluate the impact of smoking cessation and its timing in the preoperative period on postoperative morbidity in patients undergoing surgery for non-small cell lung cancer (NSCLC). Material and methods Two hundred and eighty-six patients surgically treated for NSCLC were prospectively analyzed in terms of duration and intensity of smoking, time period from smoking cessation to surgery, and postoperative morbidity. The patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Smoking may also increase pulmonary and circulatory morbidity following a variety of surgery interventions that are due to chronic bronchitis and tobacco-induced atherosclerosis of coronary arteries. Postoperative complications, according to several authors, occur 1.4-4.3 times more frequently among smokers as compared with non-smokers [31].…”
Section: Discussionmentioning
confidence: 91%
“…Smoking may also increase pulmonary and circulatory morbidity following a variety of surgery interventions that are due to chronic bronchitis and tobacco-induced atherosclerosis of coronary arteries. Postoperative complications, according to several authors, occur 1.4-4.3 times more frequently among smokers as compared with non-smokers [31].…”
Section: Discussionmentioning
confidence: 91%
“…The tobacco use metric in this study was recorded in binary fashion, with patients tabulated on the basis of whether they had endorsed active smoking within the year prior to surgery. Given that smoking cessation improves surgical outcomes, even within weeks of surgery, 12 39 this metric may have inadequately captured the timeline of tobacco use in our population. We therefore continue to feel that an emphasis on preoperative smoking cessation is critical to ensuring favorable surgical outcomes, both in our veteran population and in the population at large.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that lung cancer is the cause of 1.37 million deaths worldwide each year and that 71% of these deaths are caused by smoking, indicating that ~400,000 people die of lung cancer each year ( 15 ). Because the etiology and pathogenesis of PHC have not been determined yet, some studies ( 16 – 18 ) have shown that the diagnosis of NSCLC by genetic index is more reliable and the detection method is convenient. Therefore, it is very important to find an index that can accurately reflect the occurrence, progression and change of NSCLC and a convenient means of detection.…”
Section: Discussionmentioning
confidence: 99%